Prognostic significance of eighth edition TNM stage criteria in combined small-cell lung cancer - Zhao, Ziran; Gao, Yibo; Tan, Fengwei; Xue, Qi; Gao, Shugeng; He, Jie (Frontiers in Oncology, 2023)
Objectives: This study aimed to evaluate the prognostic significance of eighth edition TNM stage criteria in patients with combined small cell lung cancer (C-SCLC) on a population level. Methods: Using the Surveillance, Epidemiology, and End Results (SEER) database, patients diagnosed as C-SCLC (histology code 8245) between the year of 2004 and 2015 were identified. We performed Kaplan-Meier analysis and used multivariable cox regression proportional hazards model to obtain prognostic overall survival estimates of each group patients. Results: Totally, 477 patients diagnosed as C-SCLC were identified. T, N, M, TNM and combined TNM stage status of the eighth edition, were all significant prognostic factors for patients' overall survivals, best discrimination in the combined stages. Surgery was also found to be a prognostic factor (HR =1.95, 95%CI =1.49-2.56, p<0.01) for patients with C-SCLC. Conclusions: The combined eighth edition of the TNM staging criteria showed reliable prognostic significance in patients with C-SCLC. Also, surgery might be significant for improving the patients' prognosis.